Application of anti-eccentric open hydrostatic guideway in vertical lathe. (October 2019) - Zhang, Wenwu; Han, Liang; Qian, Lin
Abstract: This paper introduces an open hydrostatic guideway with anti-eccentric load structure for vertical lathe. This hydrostatic guide adopts swing plate fee-dback throttling oil supply system. The structure improves the angular stiffness of the open hydrostatic guide rail of vertical lathe, ensures the stability of the worktable in a wide range of eccentric loads, and meets the requirements of high precision machining of eccentric loaded parts.